PARQMAR (INTERREG III-B 03/MAC/4.2/M9): caracterization, planning and management of diverse marine protected areas in the Macaronesian Archipelagos. - Haroun, Ricardo J. (2013)
1st International Marine Protected Areas Congress. Geelong, Austrália, 23-27 de Outubro.